2006
DOI: 10.1038/modpathol.3800573
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of sonic hedgehog and altered methylation of its promoter region in gastric cancer and its related lesions

Abstract: The hedgehog (Hh) signaling pathway plays an important role in foregut development, and its activity is increased in various tumors, including those of the digestive tract. Our objective in the present study was to determine the pattern and extent of Sonic hedgehog (Shh) expression in gastric cancer and related lesions as well as the methylation status of its promoter region, in an attempt to clarify the regulatory mechanism of Shh expression. A total of 237 gastric cancers and related lesions (89 carcinomas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 23 publications
(32 reference statements)
1
63
2
1
Order By: Relevance
“…Recently, promoter methylation of Shh and Hh-interacting protein has been reported as another regulatory mechanism of the Hh pathway. (28,29) In ovarian carcinomas, the expression of Shh, Dhh, Ptch, Smo and Gli1 was highly correlated with cell proliferation assessed by the Ki-67 positivity index, suggesting that Hh signal molecules are actually involved in cell proliferation. To investigate further the mechanisms of Hh signaling for cell proliferation, we blocked the Hh signal pathway with cyclopamine, a known Hh pathway inhibitor, or by interfering with the mRNA expression of Gli1 in ovarian carcinoma cell lines.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, promoter methylation of Shh and Hh-interacting protein has been reported as another regulatory mechanism of the Hh pathway. (28,29) In ovarian carcinomas, the expression of Shh, Dhh, Ptch, Smo and Gli1 was highly correlated with cell proliferation assessed by the Ki-67 positivity index, suggesting that Hh signal molecules are actually involved in cell proliferation. To investigate further the mechanisms of Hh signaling for cell proliferation, we blocked the Hh signal pathway with cyclopamine, a known Hh pathway inhibitor, or by interfering with the mRNA expression of Gli1 in ovarian carcinoma cell lines.…”
Section: Discussionmentioning
confidence: 97%
“…Increased SHH expression in gastric cancer and its related lesions correlates with the altered SHH promoter methylation (Wang et al 2006). Ma et al (2006) reported that the SHH gene is amplified in esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Immunostaining of SMAD4 and SMAD2/3 was done on consecutive sections obtained from paraffin-embedded material, using mouse monoclonal anti-SMAD4 antibody (B-8; Santa Cruz Biotechnology, Santa Cruz, CA), and goat polyclonal anti-SMAD2/3 antibody (N-19; Santa Cruz Biotechnology). The experimental procedures were done as previously described (28).…”
Section: Methodsmentioning
confidence: 99%